Is lobectomy an effective treatment method in giant hepatocellular carcinomas? (Annals of Medical Research, 2021)
Aim: Hepatocellular carcinomas (HCC) are diagnosed at a high frequency worldwide. The most effective treatment method is surgery. Surgical treatment of giant HCCs (HCCs ≥10 cm in diameter) remains controversial due to its advanced stage. In this study, we discuss the surgical treatment of patients with HCC with a tumor size ≥10 cm, as well as early complications and effect on survival.Materials and Methods: Patients who underwent surgical treatment for HCC in our clinic between 2011 and 2021 were retrospectively reviewed. Patients older than ≥18 years of age who were treated with anatomical lobectomy and whose files were not missing any data were included in the study. Demographic characteristics, surgery and pathology reports, and survival data of the patients were analyzed.Results: A total of seven patients, five of whom were men, were included in the study, and the median age was 66 years (range 28–76). The median tumor diameter was 20 cm (range 10.5–24). Anatomical lobectomy was performed in all patients. The median duration of hospitalization was 4 days (range 3–7). Perioperative morbidity and mortality were not observed. At least one liver recurrence was observed in all patients during follow-up. Pulmonary metastasis was detected in two patients during follow-up. The median survival was 24 months (range 7–60).Conclusion: We think that lobectomy can be applied with low perioperative morbidity and mortality in patients with selected giant HCCs in experienced centers such as our clinic.
Keywords: Hepatocellular carcinoma; liver; lobectomy; metastasis; surgery